IMPROVING THE QUALITY OF ALUMINUM ALLOYS METHODS OF REFINING AND MODIFICATION - Mitiaiev, O. A.; Skuibida, O. L. (Science and Transport Progress, 2009)
An object under research was the refined and modified secondary aluminum alloy АК9М2. An opportunity to improve the quality of secondary aluminum-based alloys up to the level of primary aluminum alloys has been determined experimentally.